Are Institutions Conducive to Better Regulatory Environment in Infrastructure?: Empirical Study of Bangladesh and Comparison with OECD Countries. Issue 1 (March 2016) - Sumkoski, Goran
This empirical research tests the hypothesis that the institutional factors are important for achieving regulatory environment in infrastructure that is conducive to increased investment and output in a developing country such as Bangladesh. Data is obtained from ICRG, WGI and infrastructure regulation indicators from OECD database as well as from a set of uniquely reconstructed infrastructure regulatory indicators for energy, telecommunications, transport for Bangladesh for the period from 1975 to 2013 to exactly mirror the scope and depth of OECD dataset and to enable comparison. The results confirm that institutional factors such as accountability, corruption, efficiency, property rights, bureaucratic quality are conducive to better regulatory environment and positively affect infrastructure regulation in both OECD countries and in a developing country such as Bangladesh.